2018
DOI: 10.1155/2018/6406051
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Novel Porcine Derived Acellular Dermal Matrix (Mucoderm) in Peri-Implant Soft Tissue Augmentation: Preliminary Results of a Prospective Pilot Cohort Study

Abstract: Objective Over the years, several techniques have been proposed for soft tissue augmentation around dental implants in order to improve keratinized mucosa width (KMW). Recently, a porcine derived acellular dermal matrix (Mucoderm®) has been proposed as autogenous graft substitute in order to avoid palatal harvesting and obtain comparable results to connective tissue grafts, in terms of aesthetics and function. The aim of this study is to present the one-year follow-up results of this matrix in peri-implant sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 52 publications
0
32
1
3
Order By: Relevance
“…This effect may explain the results of this study obtained in the YSM model where native collagen matrices showed lower numbers of vessels and branching points in comparison to the untreated YSM. All three CM analyzed in this study are frequently used in clinical routine for soft and hard tissue regeneration and thickening procedures around teeth and dental implants with a significant benefit on keratinized mucosa width augmentation 4 weeks after implant insertion demonstrated [48]. Furthermore, a long-lasting barrier function with slow biodegradation for the porcine pericardium membrane could be shown in vitro [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect may explain the results of this study obtained in the YSM model where native collagen matrices showed lower numbers of vessels and branching points in comparison to the untreated YSM. All three CM analyzed in this study are frequently used in clinical routine for soft and hard tissue regeneration and thickening procedures around teeth and dental implants with a significant benefit on keratinized mucosa width augmentation 4 weeks after implant insertion demonstrated [48]. Furthermore, a long-lasting barrier function with slow biodegradation for the porcine pericardium membrane could be shown in vitro [4].…”
Section: Discussionmentioning
confidence: 99%
“…However, the in vivo experiments displayed better results in terms of vessel numbers and density in favor for mucoderm and collprotect matrices. A possible explanation may be seen in the fact that via the 3D architecture host cell migration and penetration could be enhanced by its interconnected structure that may lead to an increased microvessel formation and therefore angiogenesis [20,48]. However, future in vivo studies are needed to reveal a possible superiority from one bio-functionalized CM that can be recommended for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published clinical pilot study (Papi & Pompa, 2018) were not measured. However, the results of their study showed uneventful healing in all cases (n = 12).…”
Section: F I G U R Ementioning
confidence: 99%
“…A newly developed porcine-derived acellular collagen matrix (PDCM) (Mucoderm ® , Botiss gmbh, Berlin, Germany) composed of non-crosslinked natural type I and type III collagen was introduced and found to be successful for gingival augmentation and root coverage [16][17][18][19][20][21][22][23]. More recently, the matrix was proposed as an autogenous graft substitute for increasing soft tissue thickness under closed healing conditions.…”
Section: Introductionmentioning
confidence: 99%